Pengaruh Kualitas Produk Dan Promosi Terhadap Keputusan Pembelian: Studi Pada Salah Satu Usaha Konveksi di Kabupaten Bandung - Endri Adi Wibowo; Retno Resawati; Ashila Dwiyanisa; Imelda Megawati (Majalah Bisnis & IPTEK, 2022)
This research was conducted in a convection business in Bandung with the aim of knowing and analyzing the effect of product quality and promotion on purchasing decisions. The research method used is a quantitative method with a descriptive and verification approach. The sample used is respondents who have been as many as 100 people with a sampling technique. Based on the results of the study showed valid results on each item statement with a value of 0.3 and reliable by showing a value above 0.7. For Product Quality (X1) of 0.914, Promotion (X2) of 0.926, and Purchase Decision (Y) of 0.880. From the value (R Square) it is known that the effect of Product Quality (X1) and Promotion (X2) on Purchase Decisions (Y) is 0.836 or 83.6%. Product Quality (X1), Promotion (X2) and Purchase Decision (Y) are in a fairly good category. The regression coefficient value of Product Quality (X1) is 0.426. Promotion regression coefficient value (X2) is 0.397 So it can be said that purchasing decisions are influenced by Product Quality and Promotion by 83.6% while the remaining 16.4% is caused by other variables or other factors not examined. From the results of the research above, it can be concluded that product quality and promotion have a significant influence on purchasing decisions.